Sistem Monitoring dan Pengendalian Fertigasi Budidaya Cabai Rumahan Berbasis Internet of Things (IoT) - Lindawati, Lindawati; Widianty, Anggie; Rose, Martinus Mujur (Jurnal Teknologi Informasi dan Pendidikan, 2025)
This study developed an advanced Internet of Things (IoT)-based fertigation system aimed at optimizing growth and resource efficiency in contemporary agriculture. The system is meticulously designed by integrating various sensors that facilitate real-time monitoring of critical agronomic parameters such as soil moisture, temperature, nutrient concentrations, and tank solution levels. These sensors acquire essential data, which is processed using fuzzy logic to effectively manage irrigation control. Additionally, the system incorporates a mobile application, enabling remote monitoring and control, thus providing agricultural practitioners the convenience of managing their fields from any location. results from the study demonstrate a notable 30% increase in water use efficiency and a significant 25% improvement in crop yield compared to conventional manual irrigation techniques. This innovative fertigation system presents a comprehensive and effective solution for modern agriculture, supporting enhanced decision-making for crop management, reducing resource wastage, and augmenting overall agricultural productivity, thereby contributing to sustainable farming practices.